2019
DOI: 10.1073/pnas.1914704116
|View full text |Cite
|
Sign up to set email alerts
|

Cross-genotype protection of live-attenuated vaccine candidate for severe fever with thrombocytopenia syndrome virus in a ferret model

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) virus (SFTSV) is an emerging tick-borne virus classified within theBanyangvirusgenus. SFTS disease has been reported throughout East Asia since 2009 and is characterized by high fever, thrombocytopenia, and leukopenia and has a 12 to 30% case fatality rate. Due to the recent emergence of SFTSV, there has been little time to conduct research into preventative measures aimed at combatting the virus. SFTSV is listed as one of the World Health Organization’s Prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…Greater than 8000 clinical cases were reported in China by the end of 2018, and greater than1000 clinical cases had been reported in other Asian countries to date with high mortality rates ranging from 5% up to 30% [ 17 ]. Unfortunately, no efficient vaccines and antiviral drugs are available hitherto [ 13 , 18 ]. Considering the profound impact on public health, the World Health Organization has listed SFTS as one of the top ten viral diseases that require urgent and in-depth research [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Greater than 8000 clinical cases were reported in China by the end of 2018, and greater than1000 clinical cases had been reported in other Asian countries to date with high mortality rates ranging from 5% up to 30% [ 17 ]. Unfortunately, no efficient vaccines and antiviral drugs are available hitherto [ 13 , 18 ]. Considering the profound impact on public health, the World Health Organization has listed SFTS as one of the top ten viral diseases that require urgent and in-depth research [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both variants inhibited viral replication after post vaccination challenge and decreased most clinical signs. High genetic stability of the NSs knockout virus was observed even after six passages, demonstrating a low likelihood of reversion 138 .…”
Section: Therapeutics and Vaccines For Sftsvmentioning
confidence: 98%
“…The study of the rationally attenuated recombinant SFTSV demonstrated that two variants, a NSs knockout and a single amino-acid mutant can convey protection in a lethal ferret model 138 . Both variants inhibited viral replication after post vaccination challenge and decreased most clinical signs.…”
Section: Therapeutics and Vaccines For Sftsvmentioning
confidence: 99%
“…This study has fostered hope for the future design of preventive vaccines against SFTS. Moreover, Yu et al demonstrated the immunogenicity and prophylactic efficacy of attenuated recombinant SFTSV capable of triggering humoral immunity in immunized ferrets using two attenuated recombinant SFTSVs (rHB29NSsP102A and rHB2912aaNS) that contained a short 12 amino acid sequence derived from the NS open reading frame and a point mutation at position 102 that induced a proline-to-alanine substitution, respectively [ 118 ]. The study suggests that a live attenuated vaccine platform could be suitable for producing vaccine candidates against SFTSV.…”
Section: Preventionmentioning
confidence: 99%